Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s12028-010-9372-z
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Osteopontin Attenuates Brain Injury after Intracerebral Hemorrhage in Mice

Abstract: This study suggests that r-OPN may down-regulate iNOS expression by the inhibition of Stat1 phosphorylation, and therefore suppressing the MMP-9 activation, preventing ICH-induced brain injury in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Recent studies have been focused on the role of OPN in central nervous system. Administration of recombinant OPN (r-OPN) attenuated intracerebral hemorrhage-induced brain injury by suppressing matrix metalloproteinase-9 (MMP-9) activity via inhibiting inducible nitric oxide synthase (iNOS) upregulation (Wu et al, 2011). Also, r-OPN has been demonstrated to prevent early brain injury (EBI) and stabilize blood brain barrier disruption by inhibiting NF-κB dependent MMP-9 induction (Suzuki et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have been focused on the role of OPN in central nervous system. Administration of recombinant OPN (r-OPN) attenuated intracerebral hemorrhage-induced brain injury by suppressing matrix metalloproteinase-9 (MMP-9) activity via inhibiting inducible nitric oxide synthase (iNOS) upregulation (Wu et al, 2011). Also, r-OPN has been demonstrated to prevent early brain injury (EBI) and stabilize blood brain barrier disruption by inhibiting NF-κB dependent MMP-9 induction (Suzuki et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The OPN is induced within 3 hours of brain injury [37]. Furthermore, OPN increases cellular resistance to the damaging effects of nitric oxide and oxidative burst associated with inflammation by inhibiting the induction of nitric oxide synthase [37,38]. In a previous study, it has been shown that serum OPN levels are independently associated with a negative long-term outcome among acute ischemic stroke patients [9].…”
Section: Resultsmentioning
confidence: 99%
“…In an experimental study, it has been revealed that recombinant OPN prevented ICH-induced brain injury in terms of neurobehavioral tests, brain water content measurements, and neuronal cell count in the peri-hematoma region. The OPN is induced within 3 hours of brain injury [37]. Furthermore, OPN increases cellular resistance to the damaging effects of nitric oxide and oxidative burst associated with inflammation by inhibiting the induction of nitric oxide synthase [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular matrix glycoprotein osteopontin (OPN) may offer another upstream pathway of MMP-9 regulation. In a collagenaseinduced ICH mouse model, animals pretreated with recombinant OPN 20 minutes prior to ICH induction had lower levels of MMP-9 and improved clinical outcomes [54] . OPN inhibition of MMP-9 appears to occur through down regulation of inducible nitric oxide synthase, another known activator of MMP-9 [55] .…”
Section: Transcriptional Control Of Mmp Expressionmentioning
confidence: 97%
“…Using the same combined dosing regimen, GGA treatment resulted in decreased neuronal cell death and inflammatory cell migration at 72 hours post-ICH, as well as increased neurological function after ICH induction [52] . Like PDTC and dexamethasone, GGA's effect on MMP-9 may be mediated through inhibition of NF-kB; still, the exact mechanism remains uncertain since presently available research did not directly measure MMP-9 levels in the brain [53,54] . Extracellular matrix glycoprotein osteopontin (OPN) may offer another upstream pathway of MMP-9 regulation.…”
Section: Transcriptional Control Of Mmp Expressionmentioning
confidence: 99%